2018
DOI: 10.1016/j.jalz.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Military‐related risk factors for dementia

Abstract: INTRODUCTION: In recent years, there has been growing discussion to better understand the pathophysiological mechanisms of traumatic brain injury (TBI) and post-traumatic stress disorder (PTSD) and how they may be linked to an increased risk of neurodegenerative diseases including Alzheimer’s disease (AD) in veterans. METHODS: Building on that discussion, and subsequent to a special issue of Alzheimer's & Dementia published in June, 2014, which focused on military risk factors, the Alzheimer's Association co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 125 publications
0
11
0
Order By: Relevance
“…This study reports that chronic stress is clearly a risk factor for developing AD and dementia. 9, 58,59 TBIs, with or without PTSD, can increase tau deposition in the brain in veterans. 60 PTSD and TBIs are strongly associated with neurocognitive dysfunction in OIF veterans.…”
Section: Methodsmentioning
confidence: 99%
“…This study reports that chronic stress is clearly a risk factor for developing AD and dementia. 9, 58,59 TBIs, with or without PTSD, can increase tau deposition in the brain in veterans. 60 PTSD and TBIs are strongly associated with neurocognitive dysfunction in OIF veterans.…”
Section: Methodsmentioning
confidence: 99%
“…Military service as a determinant of AD neuropathology may operate broadly and distally, for example, as a marker of chronic stress risk stemming from psychological factors and chronic physical pain. [10][11][12][13][14][15][16][17][18][19][20][21][22] It may also operate more proximally and specifically as determinants tied to conditions and contexts that have lasting consequences, for example, when there is exposure to physical trauma (eg, traumatic brain injuries) and environmental hazards (Agent Orange). 10,14,16,[22][23][24] The military exposome may also expose individuals to a unique set of heightened exposures to AD risks after service (eg, cardiovascular risk factors).…”
Section: The Military Exposome: a Conceptual Foundationmentioning
confidence: 99%
“…The impact of the military exposome on AD risk can be conceptualized and researched in several ways. Military service as a determinant of AD neuropathology may operate broadly and distally, for example, as a marker of chronic stress risk stemming from psychological factors and chronic physical pain 10–22 . It may also operate more proximally and specifically as determinants tied to conditions and contexts that have lasting consequences, for example, when there is exposure to physical trauma (eg, traumatic brain injuries) and environmental hazards (Agent Orange) 10,14,16,22–24 .…”
Section: Introductionmentioning
confidence: 99%
“…TREM2 is also expressed in the microglia of the brain, regulating microglial activation and playing a multi-faceted role in its immune response [102] , [103] . Animal studies have shown that TREM2 is upregulated in the early stages following injury, making it a potential biomarker for TBI and other head injuries [104] . When microglia in the brain are activated, following injury, cleavage of TREM2 by proteases follows.…”
Section: Fluid Biomarkersmentioning
confidence: 99%
“…Therefore, elevated levels of sTREM2 are non-specific. Because upregulation of TREM2 begins early and persists over time [104] , it could prove to be a key inflammatory marker used for the diagnosis of CTE in the appropriate clinical context.…”
Section: Fluid Biomarkersmentioning
confidence: 99%